Reappraisal of Nymphoides coronata (Menyanthaceae), A 100-year-lost Species Endemic to South China - Zhou, Yadong; Xiao, Keyan; Hu, Guangwan; Zhan, Qinghua; Wang, Qingfeng (Phytotaxa, 2014)
In this paper, we reported and amended the morphological characters of Limnanthemum coronatum Dunn, which was about 100-year-lost species endemic to South China, and transferred it into Nymphoides, using a recombination name, Nymphoides coronata (Dunn) Chun ex Y.D. Zhou & G.W. Hu.